Fear and loathing in North Ossetia: how ethnic activism can turn into religious nativism - Shtyrkov, Sergei (Religion, state & society, 2023)
This contribution examines how ethnic activism in a republic of the Russian North Caucasus region, namely North Ossetia-Alania, is viewed by various social groups as a religious protest movement. This interpretation is influenced by anti-colonial discourse and an ideological agenda linking issues of religious identity and political loyalty. At the centre of these disputes are ideas about whether the ethnic religion of the Ossetian people is the local version of Orthodox Christianity or the original Ossetian religion of pre-Christian genesis that has survived to this day in the form of Ossetian ethnic traditions. Proponents of the latter concept argue that the spread of Orthodox Christianity among Ossetians should be seen as the result of spiritual colonisation by external political forces. Orthodox leaders and many ordinary believers in North Ossetia strongly protest against this interpretation of the role of Orthodoxy in the republic. Under these conditions Ossetia’s Orthodox Christians perceive any anti-colonial public gesture as aimed at contesting the completeness of their ethnic identity.